Selección del tratamiento farmacológico en el estado de mal epiléptico en niños - Silva, Marina Célia Esper; Mastroianni, Patricia de Carvalho [UNESP] (My University, 2012)
The status epilepticus (SE) is characterized by a series of crises which occur without recovery of consciousness or a single seizure lasting more than 30 minutes and can damage the central nervous system and systemic. The duration and frequency of attacks are directly related to patient prognosis. Whether seizures occur often and are longer, increase the risk of neurological and systemic complications. Child population has a higher frequency of seizures and it is associated with a lower threshold of immature brain to trigger these episodes. Aim: To determine the safest drugs prescribed for children in SE, their doses and schedules. A bibliographic survey was performed in electronic databases. Methods: The scientific health descriptors used for search was: “status epilecticus” and “anticonvulsivants” and “child”. Results: This strategy identified 396 manuscripts, of whom four were considered eligible for the study, after the assessment by floating reading and criteria. Of these, two were randomized trials and two descriptive. The studies address the use of oral midazolam, rectal diazepam and intravenous lorazepam. Conclusions: All investigated drugs were effective in treat in status epilepticus. Lorazepam is highlight, since it has fewer secondary effects and, as an alternative to the intravenous, oral midazolam. However, there is a need for further studies to demonstrate the efficacy and safety in the use of drugs in children.

El estado de mal epiléptico (EME) se caracteriza por una serie de crisis sin producirse la recuperación de la conciencia o una sola convulsión que dura más de 30 minutos1 , y se puede dañar el sistema nervioso central y sistémico. La duración y frecuencia de los ataques están directamente relacionadas con el pronóstico del paciente. Si las convulsiones se presentan con mayor frecuencia y más largas, el riesgo de secuelas neurológicas y complicaciones sisté- micas son más altas. La población infantil tiene una mayor frecuencia de las crisis y se asocia con un umbral más bajo del cerebro inmaduro para desencadenar estos episodios. Objetivo: Conocer los medicamentos utilizados más seguros para niños en EME, sus dosis y pautas. Métodos: Revisión bibliográfica de la literatura, consultando las bases de datos electrónica. Los descriptores elegidos fueron “status epilecticus” y “anticonvulsivants” y “child”. Resultados: La búsqueda resultó en 396 manuscritos, que pasaron por selección utilizando lectura flotante y criterios, lo que llevó en la identificación de 4 artículos que atendían a los criterios de inclusión. De éstos, dos eran ensayos aleatorios y dos descriptivos. Los estudios abordan la utilización de midazolam bucal, diazepam rectal y i.v., lorazepam i.v. Conclusiones: Todos los fármacos investigados fueron efectivos en el tratamiento del mal epiléptico, lorazepam destacó por tener menos efectos secundarios y, como alternativa a la vía intravenosa, el midazolam bucal. Sin embargo, hay la necesidad de más estudios para demonstrar la eficacia y la seguridad en la utilización de medicamentos en niños.
Drug treatmnet selection for status epilepticus in children
Keywords: Status epilepticus; Children; Anticonvulsant; Drug treatment; Estado de mal epiléptico; Niños; Anticonvulsivantes; Tratamiento medicamentoso